DEVELOPMENT STRATEGY FOR PALM SUGAR (CASE STUDY OF THE BUHUNG LALI FOREST FARMER GROUP, IN BUKIT HARAPAN VILLAGE, GANTARANG DISTRICT, BULUKUMBA REGENCY, SOUTH SULAWESI) - Rusli M. Rukka; Achmad Amiruddin; Husnul Khatima (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
This research was conducted in Bukit Harapan Village, Gantarang District, Bulukumba Regency with a case agrosystem, namely the ant sugar business managed by KTH Buhung Lali, this ant sugar is experiencing a few problems, namely very little local demand. This study aims to: 1) analyze the problems of the case agrosystem; 2) Analyze various solutions to problems in the context of business development; 3) Formulate actions in the target objectives; 4) Analyze the potential problems of each selected actions. Data and information obtained form informant the chairman of the farmer group and in this study were processed using the APPAS method (Agrosystem Design and Development Analysis). The results of the analysis show that the ant sugar business has a main problem, namely low sales, the main problem is caused by the low production volume and unattractive packaging. This major problem then results in low net income. To solve this problem, the main goal is to increase sales, the main target will be achieved if the amount of production increases and the packaging is more attractive, the main target efforts will have an impact on increasing sales of ant sugar, the action needed to achieve the main target is by submitting an application for investment capital assistance, buying a drying machine, procuring production space, adding manpower and designing costume packaging. The action aims to increase the net income of the ant sugar business.